Performance Evaluation of a Photovoltaic-Thermal Collector Coupled Stepped Solar Still for Indian Climatic Conditions. (18th November 2022) - Narang, Ayush; Roy, Siddhartha; Kataray, Tarun; Bonde, Vishal; Rajesh, S.; Chiranjeevi, C.; Chadha, Utkarsh; Hirpha, Bulcha Bekele
Abstract : Freshwater scarcity is increasing across many parts of the globe; to meet this demand, seawater desalination is the best choice, and the electrical energy consumption is escalating due to urbanization and industrialization. Sustainable production of electricity and freshwater can be met by an integrating photovoltaic-thermal (PVT) module with stepped solar still (SSS). The present study focuses on the theoretical modeling of the PVT-SSS desalination system for evaluating thermal efficiency, energy efficiency, freshwater productivity, and electrical power generation. The solar still productivity will be influenced by the depth of water, insulation thickness, glass cover material, thickness and inclination, and operational factors like preheating the input water supply and water salinity. A comparative analysis has been made of summer, winter, and rainy climatic conditions of Vellore town (12.9165° N, 79.1325° E), Tamil Nadu. In the present work, a thermodynamic model based on mass and energy balance is developed for the PVT-SSS system, and it is solved by a numerical method. A Runge-Kutta technique of 4th order is employed using a Python program for solving the thermodynamic simulation model. The results from the model depict that for summer, winter, and rainy climatic seasons, the freshwater productivity of PV/T-SSS was determined to be 12.18 kg/m 2 day, 6.67 kg/m 2 day, and 2.77 kg/m 2 day. Also, it is found that electrical efficiency for summer, winter, and rainy seasons is 8.91%, 9.135%, and 9.53%, respectively. A maximum and minimum freshwater production of 1668 kg/m 2 and 1218 kg/m 2 are observed for a depth of 2 cm and 5 cm, respectively.